First report on toxicity of the cyanobacterium Planktothrix rubescens isolated from a fish pond in Soc Trang province - Son, Dao Thanh; Thao, Tran Phuoc; Thu Lien, Nguyen Thi; Son, Nguyen Thanh; Trung, Bui Ba (Academia Journal of Biology, 2016)
Cyanobacteria and their toxicity are of environmental quality and ecological health concerns. This study aimed to determine the toxicity of the cyanobacterium Planktothrix rubescens from Vietnam. The cyanobaccterial samples from a fish pond in Soc Trang province were collected and brought to the laboratory for morphological species indentification and isolation for culture. The extracts of the cyanobacterium, P. rubescens, were used for microcystins characterization and toxicity testing on a micro-crustacean, Daphnia magna. The results contributed the first photos and morphological description on the cyanobacterium P. rubescens from Vietnam. The Enzyme Linked Immunoabsorbent Assay (ELISA) analysis indicated that all five strains of P. rubescens could produce microcystins at the concentrations of 0.06-0.42 µg/g dried weight. The chronic exposure of D. magna to the extract of P. rubescens, strain S1, revealed that the survival of the animal was strongly reduced. The toxicity of the extract to D. magna showed that there should be toxic sencondary metabolites other than microcystins in the extract. This study contributed the scientific information on the biodiversity and toxicity of cyanobacteria from Vietnam.